2013
DOI: 10.1111/cen.12228
|View full text |Cite
|
Sign up to set email alerts
|

Mild neonatal hyperthyrotrophinaemia: 10‐year experience suggests the condition is increasingly common but often transient

Abstract: Mild neonatal hyperthyrotrophinaemia is an increasingly common diagnosis. It is more common in males and is often transient, but predictors of success of trial-off therapy were not identified. Further studies are needed to determine optimum L-thyroxine dosing and to determine whether treatment improves neurocognitive outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…The population in this study is similar to that reported in 2002 by Calaciura et al (11), in 2008 by Leonardi et al (12) and in 2013 by Oren et al (18). Our work showed a lower prevalence of PH in children with TNH, 9.2% vs 50% in the first cited authors, 43.2% in the second, and 22.3% in the third.…”
Section: Discussionsupporting
confidence: 91%
“…The population in this study is similar to that reported in 2002 by Calaciura et al (11), in 2008 by Leonardi et al (12) and in 2013 by Oren et al (18). Our work showed a lower prevalence of PH in children with TNH, 9.2% vs 50% in the first cited authors, 43.2% in the second, and 22.3% in the third.…”
Section: Discussionsupporting
confidence: 91%
“…Here, the relative diagnostic yields of technetium and ultrasound scanning need to be specifically evaluated [50], although ectopy still needs to be ruled out, as it may be associated with only mild hyperthyrotropinemia [12,16,45]. When thyroid anatomy is normal, molecular investigations should nowadays be considered.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Also, transient hypothyroidism tends to respond to a lower dosage of L-T4 than CH. 7,15,24,25 Kashiwagura et al 26 successfully administered a suppository preparation of L-T4 in patients with hypothyroidism who could not take thyroid hormones by mouth. Because our patient was incapable of receiving oral administration of L-T4 and because intravenous and suppository preparations of L-T4 were not available at our hospital, we decided to empirically administer a rectal diluted solution of L-T4.…”
Section: Discussionmentioning
confidence: 99%